Associations between changing patterns of ST-T waves morphologies in rest electrocardiography and cardiovascular risk in an asymptomatic low risk population: a report from Ansan-Ansung cohort study. (14th October 2021) - Lee, Y; Shin, J; Park, J K; Shin, J H; Kim, H J; Park, H C; Heo, R
Abstract: Background: While clinical significance of ST-T wave abnormalities (STA) in rest electrocardiography (ECG) on long-term cardiovascular outcomes has been on debate, few studies have been reported on the association between the changes in ST-T waves in rest ECG and cardiovascular outcomes in low risk populations. We investigate the changing patterns of STA in rest ECG and the predictive value of the changes in ST-T wave in rest ECG for cardiovascular events in an asymptomatic general population. Methods: A longitudinal community-based cohort study was conducted for 12 years. Koreans aged 40–69 years were followed biennially through scheduled revisit for comprehensive assessments. Among 10, 030 participants, 6, 648 participants who did not have any cardiovascular diseases, angina-related symptoms or pathologic Q waves in rest ECG at baseline were included for analysis. Changes in STAs were defined using the changes between ECG at baseline and that at the first revisit. A major adverse cardiovascular events was defined as a composite of cardiac death, myocardial infarction, clinical diagnosis of coronary artery disease and stroke. Results: Among 5, 924 participants without STA at baseline, only 187 participants (3.2%) developed new STA. Among 724 patients (10.9%) with STA at baseline, 274 patients (37.8%) persistently showed STA at the first revisit. MACEs occurred more frequently in the participants persistently with STA and those with newly-developed STA than in the participants persistently without STA (Figure 1). Multivariate Cox-proportional hazard models showed that a higher risk of MACE was only associated with the persisted STA (HR 1.69; 95% CI 1.10–2.63). In participants with baseline STA, persisted T-wave flattening was associated with a higher risk of MACE, whereas T-wave inversion, either persisted or fluctuated was not associated with a higher risk of MACE, compared with persistent absence of STA (Figure 2). In the participants without baseline STAs, multivariate Cox-proportional hazard model showed that newly-developed T-wave flattening (HR 1.85; 95% CI 0.20–2.84), not T-wave inversion (HR 1.50; 95% CI 0.85–2.65) was associated with a higher risk of MACE. Survival receiver operating curve analysis showed that the changes in STAs had a C-index of 0.538 (95% CI 0.511–0.558), a sensitivity of 13.0% and a specificity of 92.5% and add only a small value to the predictive power of 10-year atherosclerotic cardiovascular diseases risk estimator (C-index without STA changes 0.708 [0.681–0.736] vs. C-index with STA changes 0.721 [0.694–0.748]). Conclusions: STAs uncommonly developed while frequently disappeared spontaneously in the asymptomatic general population. Persisted STA and newly developed STA in rest ECG were predictive of future cardiovascular events in the asymptomatic general population. However, the changes in STAs did not significantly improve the predictive value of the conventional risk estimator, when added. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Research Foundation of Korea